Physical and chemical characterization of Athabasca tar sands fly ash - C. O. Gomez Bueno; G. L. Rempel; D. R. Spink (Canadian Institute of Mining, Metallurgy and Petroleum, 1980)
"A morphological and chemical study of the Great Canadian Oil Sands Ltd. (GCOS) fly ash has been carried out. Extensive scanning electron microscopy, as well as light microscopy, showed that the GCOS fly ash consists of two fractions, one composed of unburnt or partially burnt irregular-shaped carbon particles and an ash fraction composed of transparent and opaque, often coloured, glassy spherical particles-some of them cenospheres (hollow spheres) and the others plerospheres (hollow spheres packed with smaller spheres). Microcrystals (0.1 to 0.3 um long) growing on the inner and outer surfaces of some of the spheres were also noted and found to contain more Fe, Ti, Ni and V than the spheres.The carbon-free GCOS fly ash particle size follows a lognormal distribution, with a geometric median particle size (by count) of3.8um and a geometric standard deviation of 1.84. IntroductionCanada's current energy situation strongly suggests that oil from the Alberta tar sands deposits will probably be recovered more extensively in the future. Today's commercially proven technology to recover oil from the Athabasca tar sands, as practised by Great Canadian Oil Sands Ltd. (GCOS), involves two major operations, namely: separation of the bitumen from the sand and upgrading of the bitumen to refinery oil; the production of significant amounts of petroleum coke and sulphur during the bitumen upgrading process. The bulk of the petroleum coke is burnt in boilers to fulfill the energy requirements of the entire operation. The boiler ash, which contains appreciable amounts of metals, such as vanadium, nickel, titanium, iron, aluminum and other elements, is collected in the boiler hoppers and cyclones of the petroleum coke-fired steam generation plants. Thus, as well as representing a petroleum resource, the tar sands represent a resource for vanadium and possibly other metals providing that metal recovery processes can be developed."